Comprehensive magnetic resonance imaging for breast cancer - N V Meladze; S K Ternovoĭ; M A Shariia; A E Solopova (Терапевтический архив, 2013)
AIM: To enhance the efficiency of diagnosis of breast tumors by comprehensive magnetic resonance imaging (MRI) involving dynamic contrast-enhanced magnetic resonance mammography (MRM) and magnetic resonance spectroscopy (MRS)/MATERIAL AND METHODS: Eighty-seven women aged 32 to 75 years with breast neoplasms were examined. MRM was performed on a Philips Achieva 3.0T TX scanner. The MRI protocol consisted of axial fat-suppressed T1- and T2-weighted spin-echo images and 8 postcontrast dynamic series. Changes in contrast-enhanced MRI of breast cancer (BC) were estimated by constructing the signal intensity-time curves. MRS was carried out using a PRESS sequence/RESULTS: Dynamic MRM determined type III signal intensity-time curve in 83.9% of the patients with BC and type II curve in 16.1% of those with breast malignancies and in 33.3% of those with breast fibroadenomas. Type I signal intensity-time curve was identified in 66.7% of the cases of fibroadenomas. Elevated choline concentrations in the malignancies were detected in 17.7% of cases. Their tumors were larger than 2 cm. The choline peak in the malignancies could not be revealed in the other cases, which was associated to the large voxel size exceeding the mass size. There was a drastic fall in the signal-to-noise ratio with smaller voxel sizes. Furthermore, higher choline levels were determined in 9.5% of the fibroadenoma cases. Comparison of MRS findings before and after contrast injection revealed the advantage of the latter, which is primarily attributed to the more accurate voxel position on the tumor than that during non-contrast-enhanced MRS/CONCLUSION: Dynamic intravenous contrast-enhanced MRM is an effective method for the differential diagnosis of breast masses. MRS cannot be included in the standard study protocol for women with breast masses for the present.